2019
DOI: 10.3390/su11205585
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Place Attachment on Environmentally Responsible Behavioral Intention and Satisfaction of Chinese Nature-Based Tourists

Abstract: Increasing visits to protected areas in China have drawn public attention on the negative impacts on ecologically sensitive areas. Understanding potential determinants of the environmentally responsible behavioral intention of nature-based tourists has become a common focus in tourism studies. Scholars seek to explore potential determinants of visitors’ behavior, and the findings can be referenced by the managers of protected areas to formulate visitor management strategies. On the basis of a sample of 402 que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 84 publications
4
36
1
Order By: Relevance
“…Most respondents were aged between 16 and 35 years, with a further 13.7% aged 36 to 55 years. Such a young profile of respondents is consistent with recent research on Dinghu Mountain (Chow et al 2019). More than half of the respondents held a college degree or higher.…”
Section: Methodssupporting
confidence: 91%
“…Most respondents were aged between 16 and 35 years, with a further 13.7% aged 36 to 55 years. Such a young profile of respondents is consistent with recent research on Dinghu Mountain (Chow et al 2019). More than half of the respondents held a college degree or higher.…”
Section: Methodssupporting
confidence: 91%
“…First of all, it is found that the residential satisfaction of our residents is significantly affected by their place dependence, social bonding and place identification while no significance is shown in affective connection overall. In this regard, localized functional dependence and social interaction of residents become the most fundamental elements in promoting residential satisfaction, which is aligned with the findings of some previous studies [27,63]. In addition, it should be noted that monthly income is found to exert great impact on residential satisfaction in the sample, and this result is significant.…”
Section: Impacts Of Place Attachment On Residential Satisfaction: Funsupporting
confidence: 88%
“…From the perspective of human-place bond, how individuals are attached to their living places, or briefly the sense of identification, is bound to exert certain significance on residents' satisfaction [27]. Chow et al [63] further clarified that deep-down place dependence and identification had a strong correlation with satisfaction. Actually, the intimate human-place relationship, or place attachment, provides a unique perspective of residents' own perceptions, especially from social, emotional and psychological aspects [27].…”
Section: Impacts Of Place Attachment On Residential Satisfactionmentioning
confidence: 99%
“…Specifically, tourists are the key actors affecting the sustainable development of tourism destinations and hotel industry (Wang et al, 2020 ). Studies in this cluster have reported that the determinants of tourists’ environment-responsible behavior include travel experience (e.g., Lee & Jan, 2015 ), place attachment (e.g., Chow et al, 2019 ), recreation experience (e.g., Lin & Lee, 2020 ), etc. Meanwhile, other stakeholders, such as management organizations and residents of tourism destinations, also play significant roles in the realization process for the sustainable tourism (e.g., Lee & Jan, 2019 ).…”
Section: Discussionmentioning
confidence: 99%